Hubungan Pola Asuh Pemberian Makan, Kebiasaan Jajan, Dan Durasi Tidur Dengan Status Gizi - Dayanti, Lestari Rahmah; Suryani, Desri; Yuliantini, Emy (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
The nutritional status of pre-school shildren is a measure of success in fulfilling nutrition in children which includes height and weight. Feeding parenting style is strongly influenced by the role of parents in regulating children’s eating patterns. Snacking habits are consumption of food or drink between main meals, and sleep duration isvery important for life because sleep has a close relationship with human health an quality of life. Snacks and sleep duration with the nutritional status of pre-school children, the population in this study were all children at Permata Bunda PAUD Bengkulu City and the sample used was 113 children. The analysis used the chi-square test. The result of the Chi Square test showed that there was no relationship between Feeding Parenting Pattern (p=0.76), Snacking Habits (p=0.62) and Sleep Duration (p=0.49) with the nutritional status of pre-school at Permata Bunda PAUD, Bengkulu City.